2016
DOI: 10.1111/fare.12181
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Pediatric Obesity: Neurobiology and Behavior

Abstract: Pediatric and adolescent obesity commonly coexist with stress‐related symptoms and disorders. Stress, the state of threatened homeostasis, is associated with the acute activation of the hypothalamic–pituitary–adrenal axis and the sympathetic nervous system. However, the chronic activation of hypothalamic–pituitary–adrenal and sympathetic nervous system axes during chronic or intense stress can lead to a variety of psychopathological and physical conditions. Behavioral and neurobiological mechanisms link chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…Genetic Regulations. There is no discounting that there are genetic and biological contributions to risk for obesity (see Pervanidou & Chrousos, 2016); however, these risks are typically modulated by the environment as genetic susceptibility to obesity will likely lead to different phenotypic outcomes because of differing exposure to and interactions within obesogenic and non-obesogenic environments over time (Rhee, Phelan, & McCaffrey, 2012). Genome-wide association studies in children and adolescents have identified more than 20 genes that place a child at risk for obesity (Salsberry & Reagan, 2010).…”
Section: Biological Regulationsmentioning
confidence: 99%
“…Genetic Regulations. There is no discounting that there are genetic and biological contributions to risk for obesity (see Pervanidou & Chrousos, 2016); however, these risks are typically modulated by the environment as genetic susceptibility to obesity will likely lead to different phenotypic outcomes because of differing exposure to and interactions within obesogenic and non-obesogenic environments over time (Rhee, Phelan, & McCaffrey, 2012). Genome-wide association studies in children and adolescents have identified more than 20 genes that place a child at risk for obesity (Salsberry & Reagan, 2010).…”
Section: Biological Regulationsmentioning
confidence: 99%
“…It is through this pathway that stress is thought to contribute (at least partially) to the increased prevalence of childhood obesity (Pervanidou & Chrousos, 2016). Identifying the types of health behaviors children and adolescents engage in is important within this critical age, because these behaviors can translate to habits which continue into adulthood (MikkilŠ, RŠsŠnen, Raitakari, Pietinen, & Viikari, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…An association between obesity and cognitive development may be particularly relevant to understand for children from low‐income backgrounds, and in particular those who have experienced high levels of stress in early life, who are at greater risk for both obesity (e.g., Miller, Dawson, & Welker, ; Pan et al, ) and academic deficits starting with lower levels of school readiness (Hackman, Farah, & Meaney, ; Pratt, McClelland, Swanson, & Lipscomb, ). Given associations between early life stress with leptin and inflammation (David, Measelle, Ostlund, & Ablow, ; Miller et al, ; Nusslock & Miller, ; Pervanidou & Chrousos, ), the negative links between obesity and cognition may be further exacerbated for children who experience higher levels of stress in early life.…”
Section: Obesity Cognition and Leptinmentioning
confidence: 99%